Research on reactive power optimization of distributed photovoltaic power distribution based on improved PSO algorithm. Issue 1 (1st November 2022) - Chen, Shuhao; Yuan, Ting; Lin, Fei
Abstract: When photovoltaic power is connected to the distribution network, its power status will change due to its instability. However, some reactive power optimization methods only optimize a single index, ignoring the overall complexity of the power grid and under the influence of the limitation of the optimization algorithm, resulting in a poor reactive power optimization effect. The improved PSO algorithm is used to study the reactive power optimization of distributed PV power distribution. The power flow of PV access is calculated by analyzing the influence mechanism of PV access. After improving the PSO algorithm by niche, Tabu search algorithm, and trigonometric function, the multi-objective reactive power optimization model was solved to realize the distribution reactive power optimization under the influence of photovoltaic access. In the experimental study of the reactive power optimization effect of the IEE333 network, the total voltage deviation of network nodes optimized by the improved PSO algorithm is reduced by about 59.06%, which effectively reduces the power grid energy damage and improves the optimization efficiency.